2007
DOI: 10.1007/s00431-007-0549-1
|View full text |Cite
|
Sign up to set email alerts
|

Mastoiditis in children: a prospective, observational study comparing clinical presentation, microbiology, computed tomography, surgical findings and histology

Abstract: histological evidence suggests that sub-acute/chronic infection underlies not only sub-acute and chronic mastoiditis, but most cases of acute mastoiditis as well. HR-CT of the temporal bone is effective in ruling out coalescence. Cranial CT is valuable in identifying intra-cranial extension. Cranial and HR-CT are recommended in the examination of children with mastoiditis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Many patients with mastoiditis were healthy prior to the mastoiditis incident, and a majority had no history of AOM. This is in accordance with other studies [5,6,9,14] where a common finding was that patients had mastoiditis in connection with the first episode of AOM.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Many patients with mastoiditis were healthy prior to the mastoiditis incident, and a majority had no history of AOM. This is in accordance with other studies [5,6,9,14] where a common finding was that patients had mastoiditis in connection with the first episode of AOM.…”
Section: Discussionsupporting
confidence: 95%
“…This was a patient whose disease was difficult to assess because of leucopenia and the result showed that it was not as severe as feared. Some authors [6,10,15] suggest that CT can be valuable in the diagnosis of complications in cases where there is no clinical improvement, or prior to surgical intervention, but when there is no clinical suspicion of complications, most cases can be managed without CT. Others propose more widely used indications for CT, as images can differentiate between periostitis and subperiosteal abscess formation, indicate infectious complication and reveal silent complications of clinical importance (e.g., sinus thrombosis and epidural abscess) in need of surgical intervention or medical treatment (anticoagulation, antibiotic choice) [12,14,16]. In an ongoing prospective study in Sweden, the occurrence and treatment of mastoiditis is closely followed and one of the key questions is the use of imaging techniques in diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These infections range from mild illnesses such as pharyngitis and impetigo to diseases of greater severity, including necrotizing fasciitis and streptococcal toxic shock syndrome (11,19,32,41,43). Thus, the organism has evolved to colonize a number of physiologically distinct host sites.…”
mentioning
confidence: 99%
“…Thus, the organism has evolved to colonize a number of physiologically distinct host sites. The role of GAS in otitis media (OM) is often underappreciated due to the effectiveness of beta-lactam antibiotics in elimination of GAS; however, there have been studies showing GAS to be one of the top 4 causative agents of OM infection and, more importantly, of development of OM complications such as acute mastoiditis (19,35,43). Mastoiditis is a severe bacterial infection of the mastoid bone and air cell system, often requiring surgical intervention and aggressive antibiotic treatment (40).…”
mentioning
confidence: 99%
“…These manifestations can be associated with conductive hearing loss due to erosion of the ossicular chain, polyp formation, otorrhoea or mastoiditis symptomatology. 17,18 • Otological symptoms may be the first sign of leukaemia or Langerhans' cell histiocytosis • In this series, 2.7 per cent of children with acute mastoiditis-like symptoms had a systemic aetiology (i.e. leukaemia or Langerhans' cell histiocytosis) • Such non-infectious 'acute mastoiditis' is a rare diagnostic and therapeutic challenge • In atypical acute mastoiditis, a non-infectious cause should be suspected • Diagnosis is aided by imaging but confirmed by histopathology…”
Section: Temporal Bone Manifestation Of Langerhans' Cell Histiocytosismentioning
confidence: 98%